Identifying Provider Barriers to the Implementation of Opioid Harm Reduction Methods: An Initial Narrative Review - Stacie A. Dee DNP, PMHNP-BC; Ketrice-Ann Delonnay DNP; Destiny Bernard DNP, PMHNP-BC; Fahimir Jean-Baptiste DNP (SAGE Publishing, 2024)
According to the Centers for Disease Control and Prevention, the opioid epidemic remains a major issue in the United States, with over 80,000 deaths attributed to opioids in 2021. This public health crisis continues to impact communities across the country, highlighting the need for intervention and reflecting the nation's failed attempts at prohibition through criminalization to reduce opioid use. Harm reduction methodshave proven to be effective in preventing adverse health outcomes and promoting the overall well-being of individuals with opioid use disorders. However, significant gaps remain in the universal implementation by healthcare providers. This review evaluated the PICOT question: What barriers exist among providers in implementing evidence-based harm reduction methods for adults aged 18 years and older, with and without opioid use disorders? A literature search was conducted across databases using key words which included: "Health care provider," "Physician," "Pharmacist," "Harm reduction," "Harm reduction programs," "Naloxone," "Buprenorphine-naloxone induction," "Methadone," "Naloxone take home kits," "Stigma," "Barriers," "Negative perception," "Refusal." The inclusion criteria focused on identifying provider barriers, specifically regarding opioid use. . The review revealed 3 major barriers that exist among providers to prevent harm reduction: stigma, lack of education and knowledge, and lack of access to resources for long-term management. Recognizing these barriers among providers can help organizations develop targeted interventions to overcome them, leading to widespread adoption of opioid harm reduction methods. The results provide an initial narrative review of the current evidence at the time of the authors search to inform practice, policy, and future research.